Hara-kiri through anal orifice: a first-of-its-kind case. - Harsh, D; Jagdeep, R; Rajendra, M (Department of Surgery, UKM Medical Centre, 2013)
Constipation and obstruction are distressing problems which not promptly treated can lead to dangerous complications. A common and potentially dangerous gastrointestinal problem is faecal impaction. Early diagnosis and prompt treatment avoids complications. Apart from manual extraction proximal and distal washout are the available options. However, the key lies in identifying the etiology of the problems and nipping it in the bud. We here present a first-of-its-kind case in which a female pulled out about 2 feet of her large intestine from her anal orifice after experiencing constipation for a period of two days. Damage control surgery was done and the patient was left with a permanent illeostomy.